Qualidade microbiológica de méis de abelhas-sem-ferrão comercializados em Coari e Tefé, Amazonas, Brasil - (:unkn) unknown (ISB - Instituto de Saúde e Biotecnologia (Coari), 2023)
Stingless bees (SB) are native to tropical and subtropical areas of the planet, but the great-est diversity is found in the Amazon region. SB honey may present common hive micro-organisms or unwanted ones, due to lack of hygiene during collection, storage and/or marketing. The objective of the research was to evaluate the microbiological quality pa-rameters of stingless bee honey sold in the interior of the Amazon. Nine samples of hon-eys were collected, five in the municipality of Tefé and four in the municipality of Coari, both purchased from street vendors. These were subjected to analysis as described in Or-dinance 253 of 2016 of the Agricultural and Forestry Defense Agency of the State of Amazonas, which establishes the Technical Regulation of Identity and Quality of sting-less bee honey, for coliforms at 45 °C, Salmonella spp. and molds and yeasts. In the ana-lyzes for molds and yeasts, the nine samples were within the quality standard, the test for Coliforms showed negative results in all samples, however four samples showed positive results for Salmonella spp, making them unfit for human consumption. Contamination by Salmonella indicates hygienic-sanitary flaws in the honey harvesting and/or processing process.
Keywords: Meliponíneos; Condições higiênico-sanitárias; Microrganismos; Parâ-metros microbiológicos; Meliponines; Hygienic-sanitary conditions; Microorganisms; Microbiologi-cal parameters; CIENCIAS DA SAUDE: NUTRICAO; Abelhas sem ferrão; Melipona; Mel - Controle de qualidade